1996
DOI: 10.1016/s0035-9203(96)90243-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum levels of reactive nitrogen intermediates and coma in children with cerebral malaria in Papua New Guinea

Abstract: Serum levels of reactive nitrogen intermediates (RNI; nitrate plus nitrite) were measured in 92 patients with cerebral malaria in the Madang Province of Papua New Guinea. RNI levels were compared to disease severity and clinical outcome, and correlated with both the depth of coma on admission and its duration. Median levels were higher among children with deeper coma than among those with lighter coma (35.6 microM vs. 16.7 microM; P = 0.008) and also among children with longer duration of coma (72 h; 59.3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Recently, much interest has been focused on the potential role of nitric oxide as a ¢nal common mediator for e¡ects of cytokine activation in malaria (Clark & Rockett 1996). Indirect measurement of levels of nitric oxide production in severe malaria has produced apparently con£icting results, with some studies apparently showing an association of high levels with poor outcome (Nu« ssler et al 1994;Al Yaman et al 1996) and others reporting the opposite e¡ect (Anstey et al 1996). However, Clark et al (1996) have argued that these results are consistent with the idea of a spectrum running from protection to pathology.…”
Section: (B) Cytokines and Severe Malariamentioning
confidence: 99%
“…Recently, much interest has been focused on the potential role of nitric oxide as a ¢nal common mediator for e¡ects of cytokine activation in malaria (Clark & Rockett 1996). Indirect measurement of levels of nitric oxide production in severe malaria has produced apparently con£icting results, with some studies apparently showing an association of high levels with poor outcome (Nu« ssler et al 1994;Al Yaman et al 1996) and others reporting the opposite e¡ect (Anstey et al 1996). However, Clark et al (1996) have argued that these results are consistent with the idea of a spectrum running from protection to pathology.…”
Section: (B) Cytokines and Severe Malariamentioning
confidence: 99%
“…The role of nitric oxide (NO), a major immune effector in malaria, described both as pathogenic 8 and protective, 9 is unclear. Technical difficulties linked to the short half-life of the radical and the impossibility of correlating peripheral measurements to in situ production are possible explanations.…”
Section: Introductionmentioning
confidence: 99%
“…In malaria, high NOx levels have been shown to be associated with worse prognosis. 46,47 However, many patients with severe illness have deranged renal function. NOx is excreted by the renal route and it has been suggested that NOx levels should be corrected for renal function.…”
mentioning
confidence: 99%